The Innovation of Public Service Mini Mall Sukodono District, Sidoarjo Regency: Inovasi Mini Mal Pelayanan Publik Kecamatan Sukodono Kabupaten Sidoarjo - Novinda Pricilia; Lailul Mursyidah (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze and describe the innovation of the Public Service Mini Mall, Sukodono District, Sidoarjo Regency and the obstacles faced in the implementation of the Public Service Mini Mall innovation, Sukodono District, Sidoarjo Regency. The research method uses descriptive qualitative, data collection is done by interview, observation, documentation and review of relevant literature. The technique of determining the informants used purposive sampling technique with the research subjects namely the Head of the General and Civil Service Subdivision, Service Staff, Service Information Officers and the community as service recipients. And the data analysis technique used is data reduction, data presentation and conclusion drawing/verification. The results of this study indicate that the novelty in the innovation of the Public Service Mini Mall, Sukodono District, Sidoarjo Regency is the first Public Service Mini Mall in Indonesia at the sub-district level. And is an expansion of public services from the Sidoarjo Regency Public Service Mall located on the East Ring Road. With this innovation that has this novelty, the community, especially the Sukodono District and surrounding areas, is easier and closer to getting public services.